Non-diphtheriae Corynebacteria Causing Breast Abscess in Nonlactating Females-Seeking to Avoid Pitfalls in Diagnosis of Chronic Breast Infections Through Diagnostic Stewardship - Sardana, Raman; Butta, Hena; Gilotra, Kirti; Mendiratta, Leena; Baweja, Pankaj; Sarin, Ramesh (Annals of Pathology and Laboratory Medicine, 2022)
Background: Consideration of non-diphtheriae Corynebacteria as an infective organism in mastitis, is usually neglected. So, infections due to Corynebacterium species may remain undiagnosed or misdiagnosed. The aim of our study was to focus on non-diphtheriae Corynebacterium as causative organisms in breast infections using scientific logic and technology of Matrix Assisted Laser Desorption Ionisation Time of Flight Mass Spectrometry (MALDITOF MS) to categorize the isolates upto species level. The clinical correlation and response to management especially targeted antimicrobials was also recorded. Methods: All the consecutive pus/tissue samples from Breast abscess received during study period were processed as per the standard guidelines. The identification of the isolate was done by automated methods. The cytopathological/histopathological and clinical details of the patients with infection due to Corynebacterium sp. were recorded and analyzed. Results: Out of 52 non-duplicate samples, five showed growth of non-diphtheriae Corynebacteria. These were identified as C. kroppenstedtii and C. amycolatum. The antimicrobial susceptibility testing showed 100% susceptibility to Amoxicillin-clavulanate, Tetracycline, Vancomycin and Linezolid for all the five isolates. Histopathological examination was suggestive of chronic inflammatory mastitis/Granulomatous mastitis. Conclusion: Non diphtheriae Corynebacteria particularly lipophilic Corynebacteria have a predilection to cause infections of breast tissue and Breast abscess which may mimic as tubercular abscess or chronic non-specific mastitis leading to unnecessary usage of antimicrobials. So, these isolates from breast tissue/pus should not be ignored rather definitely identified. This would also ensure diagnostic stewardship.